Ethnobotanical study of the plant of medicinal interest Saccocalyx satureioides Coss. & Durieu (Lamiaceae) in the region of Naâma (Algeria)) - Benaradj, Abdelkrim; Boucherit, Hafidha (Biodiversity: Research and Conservation, 2022)
An ethnobotanical study was carried out in the Naâma region to gather information on the traditional therapeutic uses of a plant of medicinal interest, Saccocalyx satureioides, practiced by the local population. Using 40 questionnaires, ethnobotanical surveys were carried out in the province of Naâma between January and April 2015. The analysis of the data collected in the field made it possible to identify 17 diseases, including hypertension, diabetes, kidney problems, certain disea-ses of the digestive tract, in particular those of the colon and the stomach, treated with S. satureioides. The results show that different parts of the plant (leaves, flowers, fruits and roots) are used in the form of decoction, maceration; they are cooked and powdered in therapeutic preparations.